2019
DOI: 10.1007/s11605-018-3953-0
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Ratio in Pancreatic Adenocarcinoma After Preoperative Chemotherapy vs. Preoperative Chemoradiation and Its Utility in Decisions About Postoperative Chemotherapy

Abstract: PCT is associated with a higher LNR and higher rates of node positivity than PCRT. Postoperative chemotherapy is associated with longer OS than observation in patients with a LNR of 0.01-0.149 after PCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 46 publications
0
23
1
Order By: Relevance
“…Second, the present study adopted PSM to adjust for selection biases for receiving either AC or noAC to create well-balanced cohorts. Finally, previous analyses 13 , 14 did not establish any survival benefit for AC in patients with low-risk disease, which was demonstrated in the present study.…”
Section: Discussioncontrasting
confidence: 63%
See 4 more Smart Citations
“…Second, the present study adopted PSM to adjust for selection biases for receiving either AC or noAC to create well-balanced cohorts. Finally, previous analyses 13 , 14 did not establish any survival benefit for AC in patients with low-risk disease, which was demonstrated in the present study.…”
Section: Discussioncontrasting
confidence: 63%
“…To date, evidence on whether AC after NAT and surgery confers incremental advantage remains an ongoing debate as several retrospective studies on this matter have yielded conflicting results. 13 18 Previous NCDB analyses by Swords et al 13 and de Geus et al 14 have attempted to study the benefit of AC following NAT. Swords et al 13 reported that AC was associated with improved survival only in patients with a lymph node ratio between 0.01 and 0.14, not in patients with node-negative disease or a lymph node ratio > 0.15.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations